2011
DOI: 10.1111/j.1537-2995.2011.03329.x
|View full text |Cite
|
Sign up to set email alerts
|

Providing ABO‐identical platelets and cryoprecipitate to (almost) all patients: approach, logistics, and associated decreases in transfusion reaction and red blood cell alloimmunization incidence

Abstract: Background There are multiple benefits to transfusing only ABO identical blood components. Historically our institution routinely transfused ABO non-identical platelets (PLTs) and cryoprecipitate to surgical patients. In April 2005, we implemented a policy of transfusing only ABO identical components whenever feasible, regardless of outdating/logistic considerations. Methods Technical staff closely monitored product usage and adjusted blood center orders based on recent utilization and planned transfusions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…In contrast, a recent study reviewed the incidence of transfusion reactions prior to and after implementing a policy of providing only ABO identical or washed PLTs [60]. The authors demonstrated that in the period after implementation of the ABO identical or washed PLT transfusion policy there were 46% fewer FNHTRs to PLT transfusions compared to the period when ABO mismatched PLTs were routinely issued.…”
Section: Part 1: Plt Transfusion and Abo Compatibilitymentioning
confidence: 99%
“…In contrast, a recent study reviewed the incidence of transfusion reactions prior to and after implementing a policy of providing only ABO identical or washed PLTs [60]. The authors demonstrated that in the period after implementation of the ABO identical or washed PLT transfusion policy there were 46% fewer FNHTRs to PLT transfusions compared to the period when ABO mismatched PLTs were routinely issued.…”
Section: Part 1: Plt Transfusion and Abo Compatibilitymentioning
confidence: 99%
“…An immunological-minded alteration of platelet transfusion practice through providing ABO-identical platelets to recipients was implemented to decrease the incidence of reactions. In a study spanning 9 years with 36 months of data collection, febrile and allergic transfusion reactions were significantly reduced after implementation of transfusion with only ABO-identical platelet components (8). …”
Section: History Of Identification Of Components Leading To Reactionsmentioning
confidence: 99%
“…Confirmation of our study's provocative findings—that ABO‐nonidentical blood is associated with worsened mortality outcomes in group A patients—could pose a dilemma for blood supply and inventory management. Prompted by reports of harm after exposure to nonidentical PLTs and cryoprecipitate, some centers have changed ordering and inventorying procedures and now provide solely identical PLTs and cryoprecipitate to patients (in addition to existing policies of providing ABO‐identical RBCs in situations where the patient's blood group is known) . These policy changes have been associated with statistically and clinically significant reductions in febrile and allergic reactions and RBC alloimmunization.…”
Section: Discussionmentioning
confidence: 99%
“…Prompted by reports of harm after exposure to nonidentical PLTs and cryoprecipitate, some centers have changed ordering and inventorying procedures and now provide solely identical PLTs and cryoprecipitate to patients (in addition to existing policies of providing ABO-identical RBCs in situations where the patient's blood group is known). 17,18 These policy changes have been associated with statistically and clinically significant reductions in febrile and allergic reactions and RBC alloimmunization. However, translating this approach to RBCs is not straightforward.…”
Section: Discussionmentioning
confidence: 99%